Pyrolysis of pine wood and characterisation of solid and liquid products - Purevsuren, Barnasan; Dashzeveg, Otgonchuluun; Alyeksandr, Ariunaa; Janchig, Narangerel; Soninkhuu, Jargalmaa (Mongolian Journal of Chemistry, 2018)
Pyrolysis of pine wood was carried out at different temperatures and the yields of solid (biochar), liquid (tar and pyrolysed water) and gas products were determined. Temperature around 500 ºC was determined as an optimal heating temperature of pyrolysis and approximately 27.1% hard residue (biochar), 21.46% tar, 20.04% pyrolysed water and 31.30% gas were obtained by pyrolysis. The thermal stability indices of pine wood are relatively low, which are indications of its low thermal stability and high yield of volatile matter (Vdaf = 90.3%). The thermal stability indices of pyrolysis of solid residue show that it is characterised by a very high thermal stability than its initial sample, for example, there was an increase of Т5% 7.7 and Т15% 3.8 times. The chemical composition of pyrolysed tar of pine wood has also been determined. Were obtained 4 different fractions with varying boiling temperature ranges of pine wood pyrolysed tar and have determined the yields of each fraction. Neutral tar was analysed by GC/MS and 20 aliphatic compounds, 25 aromatic compounds and 18 polar compounds were determined.